Influence of resveratrol in the treatment of Alzheimer's disease: a literature review (Research, Society and Development, 2022)
Introduction: Alzheimer's Disease (AD) is a neurodegenerative disease of chronic, progressive, irreversible disorder with unknown etiology, caused by the destruction of cholinergic neurons. Resveratrol is a well-studied phytochemical, existing in two isomeric forms, cis and trans; corresponds to a natural stilbenoid polyphenol of plant origin, present in high concentration in the skin of red grapes, red wine, and blueberries. This study aimed to identify the extraction, application and consumption of resveratrol in the treatment of AD. Methodology: The bibliographic research was carried out with the selection of articles, in the following databases: Periodical Capes, Pubmed, Scientific Electronic Library On-line (SCIELO) and Scholar Google (Google Scholar). Result: AD is a pathology that causes cognitive decline and represents more than half of dementia cases, especially in the elderly, causing memory and cognition loss. This disease affects approximately 10% of the elderly over 65 years of age and 40% of the elderly over 80 years of age. Resveratrol has been studied because of its antioxidant, anti-inflammatory, anticarcinogenic and neuroprotective effects. Conclusion: According to the studies analyzed, it is clear that resveratrol corresponds to an alternative for the delay and progression of AD, according to the activities or actions presented.